Tourism Entrepreneurial Prospects in Bardiya, Nepal: Challenges and Way-forwards (The Gaze: Journal of Tourism and Hospitality, 2022)
In the present context of Nepal, tourism is a new cultural expression and performance of national formation. Nepal is ready to deliberately utilize in a modern world as a means of creating a sense of identity and solidarity. The country has developed policies that directly influence and continue to shape tourism activities in Nepal. Despite plethora of literature available in Nepalese tourism sector still less has been paid attention on tourism entrepreneurial prospects and not much talked about regional and sectorial tourism prospects including Bardiya District, which is potential destination for national and international tourist for many causes. Thus, this study aims to identify tourism entrepreneurial prospects along with its challenges and potential recommendation for tourism entrepreneurial development in Bardiya District. This study is based on explanatory research design where local residents residing in Thakurbaba Municipality have been interviewed using structured questionnaire. Primary data were collected with 290 respondents selected using convenience sampling methods. Result indicates that 40% of the local people want to participate on tourism activities and want to get involved in accommodation services (31%), travel guide (26%), service foods (22%), transportation sector (18%), and other services (3%). It also finds that the major challenges in development of tourism entrepreneurship in Bardiya is lack of efficient management of transportation within the municipality and security of tourists. Hence, more investment on infrastructure will help to promote tourism entrepreneurial prospects in Bardiya.